Activity of Sulbactam-Durlobactam and Comparators Against a National Collection of Carbapenem-Resistant Acinetobacter baumannii Isolates From Greece - Petropoulou, Dimitra; Siopi, Maria; Vourli, Sophia; Pournaras, Spyros (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Acinetobacter baumannii is a leading cause of healthcare-associated infections worldwide, due to both its persistence in the hospital setting and ability to acquire high levels of antibiotic resistance. Carbapenem-resistant A. baumannii isolates (CRAB) limit the activity of current antimicrobial regimens and new alternatives or adjuncts to traditional antibiotics are urgently needed. Durlobactam is a novel broad-spectrum inhibitor of serine-type beta-lactamases that restores sulbactam (SUL) activity against A. baumannii. The sulbactam-durlobactam (SD) combination has recently completed Phase 3 testing in the global ATTACK trial. Objectives: The aim of this study is to evaluate the in vitro activity of sulbactam-durlobactam versus comparators against a representative nationwide collection of CRAB isolates. Methods: One hundred ninety CRAB isolates were collected from clinical samples of patients hospitalized in 11 hospitals throughout Greece during 2015. In vitro activities of sulbactam-durlobactam and comparators (sulbactam alone, amikacin, minocycline, imipenem, meropenem, colistin, sulbactam-durlobactam and imipenem combined with sulbactam- durlobactam) were determined by broth microdilution. Results: Durlobactam restored sulbactam activity against the majority of the strains tested, with sulbactam-durlobactam exhibiting the lowest MIC90 (8 μg/ml) relative to the other single comparators tested; 87.5% of the isolates had sulbactam-durlobactam MICs ≤4/4 µg/ml. The most active comparator was colistin (MIC90 = 16 μg/ml). The addition of imipenem further lowered the MIC90 of sulbactam-durlobactam by one two-fold dilution. Conclusions: This study demonstrated the potential utility of sulbactam-durlobactam for the treatment of infections caused by A. baumannii. If its clinical efficacy is confirmed, sulbactam-durlobactam may be an important therapeutic option for CRAB infections.